A novel 19F agent for detection and quantification of human dendritic cells using magnetic resonance imaging - Bonetto, Fernando Jose (2011)
Monitoring of cell therapeutics in vivo is of major importance to estimate its efficacy. Here, we present a novel intracellular label for 19F magnetic resonance imaging (MRI)-based cell tracking, which allows for noninvasive, longitudinal cell tracking without the use of radioisotopes. A key advantage of 19F MRI is that it allows for absolute quantification of cell numbers directly from the MRI data. The 19F label was tested in primary human monocyte-derived dendritic cells. These cells took up label effectively, resulting in a labeling of 1.7 6 0.1 3 1013 19F atoms per cell, with a viability of 80 6 6%, without the need for electroporation or transfection agents. This results in a minimum detection sensitivity of about 2,000 cells/voxel at 7 T, comparable with gadolinium-labeled cells. Comparison of the detection sensitivity of cells labeled with 19F, iron oxide and gadolinium over typical tissue background showed that unambiguous detection of the 19F-labeled cells was simpler than with the contrast agents. The effect of the 19F agent on cell function was minimal in the context of cell-based vaccines. From these data, we calculate that detection of 30,000 cells in vivo at 3 T with a reasonable signal to noise ratio for 19F images would require less than 30 min with a conventional fast spin echo sequence, given a coil similar to the one used in this study. This is well within acceptable limits for clinical studies, and thus, we conclude that 19F MRI for quantitative cell tracking in a clinical setting has great potential.